Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.52872/001c.36188
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and reporting quality of 544 studies related to ageing: a continued discussion in setting priorities for ageing research in Africa

Abstract: Background The quality assessment provides information on the overall strength of evidence and methodological quality of a research design, highlighting the level of confidence the reader should place on the findings for decision making. This paper aimed to assess the quality (methodology and quality of reporting) of ageing studies in Sub-Saharan Africa (SSA). Method This paper is the second of a Four-Part Series paper of a previous systematic mapping review of peer-reviewed literature on ageing studies cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 138 publications
0
6
0
Order By: Relevance
“…This is the third of a four-part series that aims to set priorities for aging research and practice in SSA. In the first paper, Kalu et al (2021) , provided an overview of the types and trends of aging research in the SSA context, whereas the second paper focused on the quality of reporting and methodology employed in aging research ( Kalu et al, 2022 ). A detailed description of the methodology and procedure used in the original review has been published elsewhere ( Kalu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the third of a four-part series that aims to set priorities for aging research and practice in SSA. In the first paper, Kalu et al (2021) , provided an overview of the types and trends of aging research in the SSA context, whereas the second paper focused on the quality of reporting and methodology employed in aging research ( Kalu et al, 2022 ). A detailed description of the methodology and procedure used in the original review has been published elsewhere ( Kalu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first review of longitudinal studies on aging across the SSA region, while previous reviews have mapped aging studies in SSA, with one identifying gaps and offering recommendations ( Kalu et al, 2021 ), and the other assessing the quality of reporting and methodology ( Kalu et al, 2022 ). This current study explores longitudinal aging studies as against other forms of studies such as randomized control trials because longitudinal aging studies allow us to explore relative causality and temporal understanding (tracking changes), which are associated with the aging process and have a critical role to play in policy development, evaluation, and identification of risk factors associated with aging.…”
mentioning
confidence: 99%
“…The bulk of the studies were cross-sectional involving small nonrepresentative samples whereas longitudinal studies were much fewer albeit still marred by a lack of large-scale representative samples. Overall, the review rated the methodological and reporting rigor of the studies to be of low to moderate quality particularly for qualitative studies highlighting the need for standardization in reporting and comparability of measures and indicators across studies and between countries ( Kalu et al, 2022 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…This research will build on the findings of our previous studies [ 3 , 13 , 17 ]. This study will invite panellists, including researchers, policymakers, practitioners, older adults, and family caregivers, to participate in an international e-Delphi that aims to (a) identify and prioritise aging research topic areas and methodologies relevant to the SSA, (b) identify opportunities and challenges researchers faced in conducting ageing research in SSA, and (c) explore possible solutions to tackle the challenges researchers faced in conducting ageing research in SSA.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Kalu et al conducted a systematic mapping review involving 512 ageing studies in SSA which showed that most studies focused on non-communicable diseases and HIV/AIDs, Cancer, and physical functioning [see [ 3 ] for full details]. An update study conducted by Kalu et al [ 13 ] assessed the quality of 544 articles with 25.9% being rated as fair or poor-quality. The authors suggested the need to diversify, prioritize, and improve the quality of ageing research in SSA.…”
Section: Introductionmentioning
confidence: 99%